Spontaneous peritoneal catheter knot formation: A rare cause of ventriculoperitoneal shunt malfunction. (April 2017) - Sher, Idrees; Gambhir, Shanu; Pinto, Sarah; Mujic, Asim; Peters-Willke, Jens; Hunn, Andrew
Highlights: Spontaneous peritoneal catheter knot formation is rare. The cause for this is multi-factorial including surgical technique and patient factors such as bowel kinematics. Laparoscopic assisted placement of peritoneal catheter should be considered. Abstract: Ventriculoperitoneal (VP) shunting remains invaluable in the management of hydrocephalus. It is a common procedure that can be complicated by shunt malfunction due to infection, blockage and disconnection. Spontaneous peritoneal catheter knot formation causing CSF flow obstruction is a rare phenomenon. We present a case of a 12 years old boy with spontaneous knot formation in the peritoneal catheter causing VP shunt obstruction and hydrocephalus.